Can debt be sustainable, if life isn't? Argentina's debt crisis and social reproduction - Féliz, Mariano (2023)
The cycle of external indebtedness of dependent countries has become a huge constraint on any strategy for radical social change. Argentina has recently entered a new process of debt overhang and renegotiation with the International Monetary Fund and private global creditors. The dominant debate around the country's foreign debt revolves around the conditions that can guarantee the sustainability of repayment. The underlying objective is to remain in the debt system that produces and reproduces dependency. This chapter will seek to analyze the question of debt sustainability from another point of view: Is it possible to guarantee the (financial) sustainability of the debt at the same time as guaranteeing the sustainability of life? Our argument is that by remaining in the global debt system, Argentina creates conditions that violate the requirements for the sustainability of human and nonhuman life. Drawing on a discussion from Marxist dependency theory and the traditions of Marxist feminism and environmentalism, we will discuss how the debt sustainability argument presupposes the impossibility of reproducing life. In particular, we will show how the conditions required to guarantee debt sustainability in Argentina entail the deepening of the superexploitation of the "productive" and "reproductive" labor force, and the exacerbation of extractivism, putting social reproduction in crisis.